(untitled) (Música Hodie, 2025)
This study aimed to explore how cultural context shapes emotional expressiveness in vocal art by comparing chamber and opera performances from China and Ukraine. The study employed an interdisciplinary methodology that integrated tools from musicological analysis, psychological interpretation of affect, and cultural semiotics. A qualitative analysis was conducted on four selected stage performances using video recordings accessed from open sources between January 2022 and May 2025. The study found that the Chinese vocal tradition was characterised by a contemplative type of emotionality, which was manifested in restrained dynamics, subtle intonation shifts, smooth phrase development, and semantically rich melismas. The origins of this style were linked to the philosophical concept of inner harmony, the ritualised nature of opera, and the gradual adaptation of Western techniques to local performance aesthetics. Examples of contemporary Chinese chamber singing (for example, Zhou Shen) demonstrate the preservation of a restrained technique while enhancing emotional intensity. The Ukrainian vocal tradition was oriented towards emotional openness and drama, which was shaped by folk song culture, liturgical singing and academic opera. In the stage interpretations of Ukrainian performers (in particular, in wartime), there was an emphasis on culminating moments, contrasting dynamics and a pronounced social connotation of emotional content. The practical significance of the study lies in the possibility of applying the results obtained for the development of intercultural vocal pedagogy, improvement of interpretive strategies and preparation of vocal training programs in a globalized artistic context.